Idiopathic dilated cardiomyopathy: lack of association with hepatitis C virus infection. Issue 3 (1st September 1998) - Dalekos, G N; Achenbach, K; Christodoulou, D; Liapi, G K; Zervou, E K; Sideris, D A; Tsianos, E V
Abstract : Objective: To determine whether there is an association between hepatitis C virus (HCV) infection and dilated cardiomyopathy in a well defined area of north western Greece; such an association has been reported elsewhere. Design: Evaluation of consecutive patients with chronic HCV infection for the presence of clinical or subclinical manifestations of dilated cardiomyopathy by history, physical examination, and non-invasive laboratory procedures (ECG, chest x ray, and echocardiography) before the initiation of interferon α treatment; investigation for HCV infection markers in patients with dilated cardiomyopathy by enzyme and immunoblot assays (antibodies to HCV) and the reverse transcriptase polymerase chain reaction (HCV RNA). Setting: A tertiary referral centre for patients with chronic hepatitis and dilated cardiomyopathy. Patients: 102 patients with well defined chronic HCV infection and 55 patients with well established dilated cardiomyopathy were evaluated. Main outcome measures: The need for HCV testing in patients with dilated cardiomyopathy, or follow up for heart disease in patients with chronic HCV infection. Results: None of the patients with chronic HCV infection had clinical or subclinical evidence of dilated cardiomyopathy from history and laboratory findings. None of the patients with dilated cardiomyopathy was positive for antibodies to HCV or viraemic on HCV RNA testing. Conclusions: The study neither confirms the findings of other investigators, nor indicates a pathogenic link between HCV and dilated cardiomyopathy. For this reason, at least in Greece, testing for HCV in patients with dilated cardiomyopathy or follow up for heart disease in HCV patients appears unnecessary. Genetic or other factors could be the reason for this discrepancy if previously reported associations between HCV and dilated cardiomyopathy or hypertrophic cardiomyopathy were not coincidental.